2021
DOI: 10.1007/s00775-020-01840-w
|View full text |Cite
|
Sign up to set email alerts
|

The Asp1 pyrophosphatase from S. pombe hosts a [2Fe-2S]2+ cluster in vivo

Abstract: The Schizosaccharomyces pombe Asp1 protein is a bifunctional kinase/pyrophosphatase that belongs to the highly conserved eukaryotic diphosphoinositol pentakisphosphate kinase PPIP5K/Vip1 family. The N-terminal Asp1 kinase domain generates specific high-energy inositol pyrophosphate (IPP) molecules, which are hydrolyzed by the C-terminal Asp1 pyrophosphatase domain (Asp1365−920). Thus, Asp1 activities regulate the intracellular level of a specific class of IPP molecules, which control a wide number of biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…These strategies are not limited to proteins containing one [4Fe-4S] cluster. We have previously shown that the same strategies can be applied for the maturation of a [2Fe-2S] protein [83]. In addition, we have demonstrated that this approach can be also used for radical SAM enzymes.…”
Section: Discussionmentioning
confidence: 90%
“…These strategies are not limited to proteins containing one [4Fe-4S] cluster. We have previously shown that the same strategies can be applied for the maturation of a [2Fe-2S] protein [83]. In addition, we have demonstrated that this approach can be also used for radical SAM enzymes.…”
Section: Discussionmentioning
confidence: 90%
“…Relatively few cytosolic [2Fe-2S] proteins per species are known to date (Fig. S1) (4,19,(29)(30)(31)(32)(33). In addition to true target proteins, also the cGrxs and the early CIA components Dre2, Cfd1, and Nbp35 have been reported to (transiently) bind [2Fe-2S] clusters in vitro (and in cellulo for Dre2) suggesting that also these proteins are acceptors of binuclear clusters (26,(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
“…S1 ). Relatively few cytosolic [2Fe-2S] proteins per species are known to date ( 4 , 19 , 29 33 ). In addition to true target proteins, also the cGrxs and the early CIA components Dre2, Cfd1, and Nbp35 have been reported to (transiently) bind [2Fe-2S] clusters in vitro (and in cellulo for Dre2) suggesting that also these proteins are acceptors of binuclear clusters ( 26 , 34 37 ).…”
mentioning
confidence: 99%